Media Framing of Sustainable Development In Indonesia’s New Capital: A Comparative Analysis of Antaranews.com and Tempo.co Using Entman’s Model - Syahira, Fatihani; Romadlan, Said; Pamungkas, Andhika (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This article investigates how two leading Indonesian online news outlets, Antaranews.com (state-owned) and Tempo.co (independent), frame the issue of sustainable development in Indonesia’s new capital, Ibu Kota Nusantara (IKN). Employing Robert Entman’s four-element framing model and the Hierarchy of Influences Theory, the study uses a qualitative content analysis of 54 news articles published in January 2025, complemented by in-depth interviews and literature review to triangulate findings. Results show that Antaranews.com frames IKN predominantly through positive narratives, emphasizing government achievements, infrastructure readiness, and inter-agency synergy, while downplaying risks and criticism. This approach reflects its organizational role as a state information agency and is supported by routines that prioritize official sources and state agendas. In contrast, Tempo.co adopts a more critical and pluralistic framing, drawing attention to project delays, policy ambiguities, and potential social and environmental impacts. Tempo.co’s coverage features a broader array of sources, including academics, parliamentarians, and community representatives, reflecting its editorial independence and investigative ethos. The study concludes that differences in framing are shaped by ownership structure, newsroom culture, and broader political and economic contexts. These findings highlight the importance of media pluralism and editorial independence for robust public discourse and effective communication on strategic national projects in Indonesia.